2014
DOI: 10.1080/03069885.2014.975676
|View full text |Cite
|
Sign up to set email alerts
|

‘If you look the part you’ll get the job’: should career professionals help clients to enhance their career image?

Abstract: This article presents a critical exploration of the role of career professionals in supporting people to reflect on and enhance their appearance, attractiveness and self-presentation (career image). The article is conceptual and based on a review of the broader literature on career success, appearance and attractiveness. It explores the evidence for a relationship between attractiveness and career, and the authors propose a conceptual framework in which career image is comprised of three elements (interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Hartas (2011) states that economic advancement of the families often provides children with opportunities for school choice, an improved learning environment and leisure to engage in educational activities. On the other hand, education offers opportunities for placing oneself in a better job and enhancing economic status (Hooley & Yates, 2015). Asserting these relationships between education and economy, Dalit experiences with obstacles to education, in my study context, also were observed in a similar line.…”
Section: Facing Economic Problemsupporting
confidence: 60%
“…Hartas (2011) states that economic advancement of the families often provides children with opportunities for school choice, an improved learning environment and leisure to engage in educational activities. On the other hand, education offers opportunities for placing oneself in a better job and enhancing economic status (Hooley & Yates, 2015). Asserting these relationships between education and economy, Dalit experiences with obstacles to education, in my study context, also were observed in a similar line.…”
Section: Facing Economic Problemsupporting
confidence: 60%
“…They imagined that these judgements would be made both as a series of discrete assessments (does your hair look smart? ), but also as an overall assessment regarding career image (Hooley and Yates, 2014) and the ability to perform an identity that fits with both graduate and worker roles.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that there is a range of career benefits for those who present themselves in a way that is appealing to their colleagues and employers. Hooley and Yates (2014) summarize this literature, arguing that an advantageous career image comprises physical beauty, inter-personal skills and aesthetic self-presentation.…”
Section: Graduate Transitions and The Performance Of Identitymentioning
confidence: 99%
“…Erotic capital used to investigate beauty-related business, entertainment industry, service economies such as sale work and managerial positions, and career image development for job searching (e.g., Frew & McGillivray, 2005;Hooley & Yates, 2014, Mears, 2014. For many scholars, erotic capital is performed and developed by consumers by centrally intertwining with consumption (Sarpila, 2013).…”
Section: Erotic Capital As a Resource Inmentioning
confidence: 99%